Literature Review: Potensi Senyawa Bahan Alam sebagai Inhibitor HMG-CoA Reduktase untuk Terapi Kolesterol - Khansa Aliifah; Hilma Marisa; Indah Lestari; Jelita Septiani; Jihan Al Ihsani; Muhamad Iqbal Rhamadianto (Lembaga Pengembangan Kinerja Dosen, 2025)
Hyperlipidemia is a condition in which lipid levels in the bloodstream (plasma) experience an imbalance in lipid levels, although it does not show severe symptoms but can trigger various serious diseases. Statins are used as the main therapy for antidyslipidemia, but with long-term use, statins cause various side effects such as muscle pain, muscle disorders and muscle discomfort. Indonesia has a variety of plants that have benefits for lowering blood cholesterol levels. To determine the potential of metabolite compounds contained in several plants as HMG-COA Reductase inhibitors, research can be carried out using molecular docking. The purpose of this literature study is to determine the comparison of compounds that have HMG-COA Reductase inhibitor inhibitor activity. The method used in compiling this literature study is from various national and international scientific articles published in the period 2020-2025. The natural compounds that have been studied have significant inhibitory activity against the HMG-CoA Reductase enzyme, namely from the 10 plants studied, Rhodomyrtus tomentosa has the best activity in inhibiting the HMG-CoA Reductase enzyme with an Affinity of the Binding value of -11.4 so that it has the potential to be further developed as a natural anti-cholesterol drug.